Antibiotic use in a level three NICU in South Africa - Wireko, Brobby Naana (Division of Neonatology, 2019)
Background: Antibiotics are the most commonly used medications in the neonatal intensive care unit, and when used appropriately, can be lifesaving in the NICU. However, their inappropriate use has been found to be associated with certain adverse effects like Late Onset Sepsis, Necrotizing Enterocolitis, Chronic lung disease, Candidiasis, antibiotic resistance and death. Objective: This study seeks to describe the current antibiotic practices and management of neonatal sepsis including antibiotic use in a level III Neonatal unit in South Africa Method: The study was conducted at the Groote Schuur Hospital Neonatal Unit in South Africa which provides both emergency and continuous care for neonates in the Western Cape Province. All positive cultures as well as the duration of antibiotics within the period of 1st January 2016 to 31st December 2016 at the GSH Neonatal Unit were entered into a database. Data on infection and antibiotic use in Very Low Birth weight infants was extracted from the Vermont Oxford Network (VON) database. The GSH Neonatal Unit is one of the contributing units to the VON database. This was in addition to 2 Quality audits on antibiotic use in the unit done on 2 separate days in the months of February and November in 2016. The 10 month interval between the 2 audits was to allow for any policy changes to be implemented based on a series of educational webinars for staff that were organized during that period. Another audit was done in a randomly selected month collecting data of all infants on antibiotics for the entire month. Results: The overall incidence rates of Early and Late onset sepsis among the VLBW infants were 1.0% and 5.2% respectively with the 24 – 26 week Gestational age category having the highest rates. GBS and Klebsiella pneumonia were the leading pathogens for EOS and LOS respectively. The incidence of sepsis among babies bigger than 1500g was 0.52%.The commonly used antibiotics were Ampicillin, Gentamycin and Meropenem, which were consistent with the Unit‟s protocols. The major reasons for continued use of antibiotics beyond 48 hours were clinical signs concerning for risk of sepsis, pending culture results and laboratory results concerning for risk of sepsis. Regarding infants who received antibiotics for more than 48 hours, vii a comparison of both audits showed GSH plotting below the lower quartile at 30% in the 1st audit, and at 67% between the median and the lower quartile in the 2nd audit. Discussion: Gestational age has always been a universal risk factor for neonatal sepsis, and this was confirmed in this study. Inappropriate use of antibiotics in neonates arises on account of the difficulty clinicians face because of the nonspecific and vague nature of the signs of neonatal sepsis, especially in the VLBW category. Additional biomarkers for sepsis are increasingly being used to aid in the decision of whether or not to discontinue antibiotics after 36 - 48 hours. Conclusion: There is the need for stricter antibiotic stewardship to reduce the inappropriate use of antibiotics among neonates. Antibiotics being used at GSH are appropriate for the prevailing organisms although there are some resistant organisms.